2020
DOI: 10.1155/2020/8859017
|View full text |Cite
|
Sign up to set email alerts
|

Role of PPARs in Progression of Anxiety: Literature Analysis and Signaling Pathways Reconstruction

Abstract: Peroxisome proliferator-activated receptor (PPAR) group includes three isoforms encoded by PPARG, PPARA, and PPARD genes. High concentrations of PPARs are found in parts of the brain linked to anxiety development, including hippocampus and amygdala. Among three PPAR isoforms, PPARG demonstrates the highest expression in CNS, where it can be found in neurons, astrocytes, and glial cells. Herein, the highest PPARG expression occurs in amygdala. However, little is known considering possible connections between PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 171 publications
0
6
0
Order By: Relevance
“…Thus, inhibiting the activation of the JNK/p-JUN signaling pathway may have a positive impact on neuroprotection and cognitive function improvement. Peroxisome proliferator-activated receptor gamma (PPARG) is a nuclear receptor, proven to play a key role in regulating in ammatory responses and oxidative stress responses (Rudko et al 2020). PPARG signaling can enhance neuroplasticity and neural repair by affecting BDNF(Gold 2021).Kae , acts upon Peroxisome Proliferator-Activated Receptor Gamma (PPARG), curbing the generation of in ammatory mediators through an upregulation of PPARG expression, thus positively contributing to neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inhibiting the activation of the JNK/p-JUN signaling pathway may have a positive impact on neuroprotection and cognitive function improvement. Peroxisome proliferator-activated receptor gamma (PPARG) is a nuclear receptor, proven to play a key role in regulating in ammatory responses and oxidative stress responses (Rudko et al 2020). PPARG signaling can enhance neuroplasticity and neural repair by affecting BDNF(Gold 2021).Kae , acts upon Peroxisome Proliferator-Activated Receptor Gamma (PPARG), curbing the generation of in ammatory mediators through an upregulation of PPARG expression, thus positively contributing to neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Other pathways such as PPAR signaling, VDR/RXR signaling, and corticotropin-releasing hormone signaling pathway were more significant in the early stage after SPS&FS exposure. PPAR signaling was indicated as actively regulating genes associated with lipid and carbohydrate metabolism ( Thibaut, 2017 ), and two other mechanisms were observed to contribute to anxiety formation: (1) neuroinflammation and gene expression of cytokine and (2) the hydrolysis of neuropeptide CCK-4 ( Domi et al, 2016 ; Rudko et al, 2020 ). Recent studies have suggested PPAR-α, which engages in neurosteroid biosynthesis, is especially critical for the regulation of emotion in PTSD and depression ( Locci and Pinna, 2019 ; Nisbett and Pinna, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the result of PPI network, AR and ESR1 are associated with a variety of human behaviors, including anxiety [30]. PPARG has been con rmed to be associated with pathological anxiety [31]. glucocorticoid receptor (NR3C1) [32] and HTR2A [33] are also associated with anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%